2008
DOI: 10.1016/j.peptides.2008.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-like effect of neuropeptide S in the rat defensive burying

Abstract: Neuropeptide S (NPS) has been recently identified as the endogenous ligand of a previously orphan G-protein-coupled receptor now named NPSR. Both NPS and its receptor are expressed in the brain, where they modulate different functions. In particular, it has been demonstrated that intracerebroventricular (i.c.v.) injection of NPS in rodents increases wakefulness and promotes anxiolytic-like effects. In the present study we used the defensive burying (DB) test in rats to further investigate the action of human N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
65
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 33 publications
10
65
0
Order By: Relevance
“…1,2 Recent evidence from rodent models indicates that the NPS system is critically involved in the regulation of unconditioned and conditioned fear behaviors. 1,[3][4][5][6][7] In humans, the locus for the NPS receptor gene NPSR1 maps to a chromosomal region that has reproducibly been linked to PD, with those markers creating the highest lod scores lying in close vicinity to he NPSR1 locus. [8][9][10] NPSR1 contains a frequent A>T polymorphism (rs324981) that codes for an Asn/Ile change at position 107.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recent evidence from rodent models indicates that the NPS system is critically involved in the regulation of unconditioned and conditioned fear behaviors. 1,[3][4][5][6][7] In humans, the locus for the NPS receptor gene NPSR1 maps to a chromosomal region that has reproducibly been linked to PD, with those markers creating the highest lod scores lying in close vicinity to he NPSR1 locus. [8][9][10] NPSR1 contains a frequent A>T polymorphism (rs324981) that codes for an Asn/Ile change at position 107.…”
Section: Introductionmentioning
confidence: 99%
“…This may be indicative of a complex pharmacological profile of NPS, the effects of which depend on the dose tested. On the other hand, several studies have shown selective NPS effects at ICV doses as high as 10 nmol (Beck et al, 2005;Smith et al, 2006;Vitale et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest the possibility that the NPS system plays an active role in mediating behavioral adaptations associated with protracted withdrawal. Considering that activation of NPS receptors by the endogenous ligand results in marked anxiolytic action (Leonard et al, 2008;Rizzi et al, 2008;Vitale et al, 2008;Xu et al, 2004Xu et al, , 2007 and that NPS injection in the amygdala exerts anxiolytic effects (Jungling et al, 2008), one could interpret the increased NPSR expression in this brain area as an attempt to compensate for the increase in anxiety occurring in animals with a history of ethanol dependence. On the other hand, it should be also pointed out that ethanol intoxication may represent a potent stressor per se (Breese et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it would be highly interesting to study the possible link between the NPS system, alcohol withdrawal, and anxiety, given that on the one hand, NPS is related to anxiolytic-like actions (Leonard et al, 2008;Vitale et al, 2008), while on the other, it activates the HPA axis and increases relapse to alcohol and cocaine seeking elicited by conditioning factors and drug priming, respectively (Cannella et al, 2009;Paneda et al, 2009). …”
Section: N Europeptide S (Nps) Is the Recently Discovered Endogenous mentioning
confidence: 99%